STATISTICAL METHODS FOR EVALUATING EXPERIMENTAL DATA ON THE USE OF MATHEMATICAL COMPETENCIES IN STUDY FOR A RESILIENT ECONOMY - Petruk, Vira; Prozor, Olena; Sabadosh, Yuliia; Baranovska, Iryna; Palii, Maksim; Moroz, Yevheniia; Kumargazhanova, Saule; Mussayeva, Dinara (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2023)
The description of the problems, solved within the statistics evaluation of the results of educational (pedagogical) experiment in resilient economy is given. Comparison of the two average samplings and hypothesis verification relative to dispersions of the two samplings are considered. It is shown the hypothesis that teaching and methodical training system of subjects of higher mathematics in technical universities, suggested on the base of the modern interactive technologies, significantly improves the quality of the base level of professional competence of future engineers. The methods for statistical processing of the obtained results, which very thoroughly research all the indexes which compose the suggested learning and methodical system for teaching higher mathematics in technical universities are used.